Seasonal Variation Characteristics of C, N, and P Stoichiometry and Water Use Efficiency of Messerschmidia sibirica and Its Relationship With Soil Nutrients - Li, Tian; Zhang, Zehao; Sun, Jingkuan; Fu, Zhanyong; Zhao, Yinghan; Xu, Wenjing (Frontiers in Ecology and Evolution, 2022)
The seasonal dynamic characteristics of C, N, and P stoichiometry and water use efficiency (WUE) of Messerschmidia sibirica and the soil in the Yellow River Delta (YRD) were studied. The correlations of stoichiometric characteristics and WUE between organs of M. sibirica and soil were analyzed. The results showed that: (1) the contents of C, N, and P and their stoichiometric ratios in various organs of M. sibirica varied with seasons. The seasonal dynamics of leaf N:P showed that the degree of nutrient restriction by N decreased in July and increased in September. (2) The contents of C, N, and P, as well as their stoichiometric ratio, showed a high correlation throughout the growing season, with N:P showing a significantly positive correlation among organs and the lowest stoichiometric correlation between leaf and root. (3) C13 stable isotope analysis showed that the WUE of M. sibirica in May was significantly higher than that of other months (July and September). The WUE had a significantly positive correlation with leaf C and N content and a significantly negative correlation with leaf C:N, indicating that M. sibirica can compensate for the decline in N use efficiency through the improvement of WUE. The structural equation model (SEM) showed that the leaf N and P contents were affected by the joint effect of season and WUE, and the leaf C content was mainly directly affected by WUE. (4) Redundancy analysis (RDA) analysis showed that soil P content and soil N:P were the main factors affecting the variation of stoichiometry and WUE in various organs of M. sibirica. This study is helpful to deeply understand the adaptive mechanism of plant nutrient and water use, which provides a theoretical basis for vegetation protection and restoration in the study area.